Vir energije pulzarjev - Hočuršćak, Lara (Matrika, 2017)
In this article first pulsar discovery is presented and what is the mechanism that enables us to observe them. Knowing a pulse period and some of pulsar's important properties, one can calculate the important quantities that are essential to describe a star. We use the lighthouse model to explain why pulsars emit electromagnetic radiation which enables us to detect them. ?$P\dot{P}$? diagram is a tool that helps us study the birth, life and death of a pulsar or even the rebirth as a millisecond pulsar. It enables us to follow a life of a star from a know pulse period and its changing. The Crab pulsar with its precisely known age will be helping us test the equations from a known pulse period and its time derivative.
Keywords: observations; opazovanje; pulsars; pulzarji